2014
DOI: 10.1074/jbc.m114.553321
|View full text |Cite
|
Sign up to set email alerts
|

Decreased O-Linked GlcNAcylation Protects from Cytotoxicity Mediated by Huntingtin Exon1 Protein Fragment

Abstract: Background:Earlier reports indicate that O-GlcNAcylation might be protective in neurodegenerative disorders. Results: Suppressing O-GlcNAcylation modulates autophagy to enhance the viability of neuronal cells expressing cytotoxic mutant huntingtin exon 1 protein (mHtt). Conclusion: O-GlcNAcylation regulates the clearance of mHtt by modulating the fusion of autophagosomes with lysosomes. Significance: This regulatory mechanism emerges as a novel therapeutic strategy for Huntington disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 53 publications
3
50
0
1
Order By: Relevance
“…of the unfolded protein response, and endoplasmic reticulum stress (59), decreased proteasomal degradation (60), or blunted cellular autophagy (61,62). Although mechanistically reasonable, further studies are needed to determine the process by which HGϩGNS increases chronic insulin secretion and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…of the unfolded protein response, and endoplasmic reticulum stress (59), decreased proteasomal degradation (60), or blunted cellular autophagy (61,62). Although mechanistically reasonable, further studies are needed to determine the process by which HGϩGNS increases chronic insulin secretion and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has recently been shown that suppression of O-GlcNAcylation by overexpression of OGA led to decreased p62 and increased LC3-II, suggesting an enhanced autophagic flux. Azaserine inhibits glutamine fructose-6-phosphate amidotransferase, one of the key enzymes of hexosamine biosynthesis pathway, and thereby leads to decreased O-GlcNAcylation and a decrease of LC3-II and p62 in Neuro2A cells, attenuating toxicity by mutant HUNTINGIN exon 1 fragment in these cells (71). …”
Section: Regulation Of Autophagy By O-glcnacylationmentioning
confidence: 99%
“…In C. elegans , mutations in O-GlcNAc cycling enzymes resulted in elevated levels of GFP::LGG-1 (homolog of Atg8 and LC3) upon starvation [87, 88]. In contrast to observations in tauopathy models, O-GlcNAcylation plays a detrimental role against mutant huntingtin toxicity in cells and fly models, as demonstrated by either overexpression of OGT or OGA, or by pharmacological alterations of O-GlcNAc levels using azaserine or glucosamine [89]. Decreasing O-GlcNAcylation enhances the fusion of autophagosomes with lysosomes, thereby elevating autophagic flux.…”
Section: O-glcnacylation Apoptosis and Autophagymentioning
confidence: 99%
“…Decreasing O-GlcNAcylation enhances the fusion of autophagosomes with lysosomes, thereby elevating autophagic flux. This is associated with decreased mHtt aggregates in flies (Fig.5A) [89]. Autophagy inhibition may be mediated by O-GlcNAcylation of the SNARE protein SNAP29, inhibiting autophagosome-lysosome fusion and autophagic flux [90].…”
Section: O-glcnacylation Apoptosis and Autophagymentioning
confidence: 99%